Family Violence and Adolescent Aggressive Behavior: The Direct and Indirect Effects of Depression and Substance Use. - Lawrence, Timothy I.; Merrin, Gabriel J.; Mcfield, Ariel A. (International Journal of Mental Health & Addiction, 2025)
Prior literature suggests exposure to family violence often leads to aggressive behavior among adolescents. Despite this association, little is known of the potential explanatory variables that could link exposure to family violence and aggressive behavior, such as substance use and depressive symptoms. Thus, guided by the intergenerational transmission of violence theory, this cross-sectional study used data from the Bullying, Sexual, and Dating Violence Trajectories From Early to Late Adolescence in the Midwestern United States, 2007–2013, to test whether exposure to family violence is associated with aggressive behavior. Then, using structural equation model, this study explored whether depressive symptoms and substance use sequentially explained the relationship between exposure to family violence and aggressive behavior. A total of 1162 adolescents (M = 12.29), 52.1% males and 47.9% females, participated. Results show that exposure to family violence positively associated with aggressive behavior. Although sequentially, substance use and depressive symptoms did not explain the relationship between exposure to family violence and aggressive behavior, substance use alone had a significant indirect effect on the relationship between exposure to family violence and aggressive behavior. Therapeutic and theoretical implications are discussed.